(untitled) (KYAMC Journal, 2021)
A 20-year old non-diabetic non-hypertensive non-smoker male farmer presented with purulent umbilical discharge for one year. He used to live an unhygienic life. He had throbbing pain, intermittent fever preceded by chills and rigors for fifteen days. He was treated with various antibiotics, analgesics, antipyretics for a long time by local physicians. But he was not cured. The umbilical and periumbilical area were found inflamed, edematous and red with a palpable small hard infra umbilical mass. The mass was irreducible, non-pulsatile, non-compressible and not trans illuminating with no visible and no palpable impulse on coughing. Just prior to incision, a probe was introduced through the umbilicus that had not passed beyond the abdominal wall into the peritoneal cavity indicating that it was a sinus and not a fistula.The infra-umbilical smile incision was deepened and a flap was raised upwards until multiple small calculi of variable consistency were found at a depth. These were extracted. The sinus tract and the accompanying small abscess cavity were excised and sent to the laboratory for culture and sensitivity tests, histopathological examination and other relevant tests. The studies revealed Staphylococcus aureus sensitive to gentamycin and amikacin. The histopathological examination revealed acute inflammatory cells with no granuloma and no malignancy. The patient was given parenteral antibiotics as per the sensitivity test result plus metronidazole against possible anaerobic co-infection. The post-operative period was smooth and uneventful. We like to share our experience of managing this very rare disease of umbilical lithiasis. KYAMC Journal.2021;12(02): 111-113